2019
DOI: 10.1111/cid.12844
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of high performance polymers and new generation cubic zirconia used for implant‐supported fixed, cantilevered prostheses

Abstract: BackgroundThe load‐to‐failure performance of computer‐assisted design and computer‐assisted manufacturing (CAD‐CAM) high performance polymers (HPP) and new generation cubic zirconia (Zir) material when used with titanium (Ti) bases for implant‐supported fixed prostheses with cantilevers is unknown.PurposeTo evaluate the load‐to‐failure performance of different CAD‐CAM fabricated HPP and a new generation cubic Zir in a cantilevered situation when used with Ti bases.Materials and MethodsFive specimens with a Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…On the other hand, Preis et al in a fatigue testing of PEEK molar crowns either bonded or screw-retained found lower fracture resistance than zirconia ones, while a total failure rate was observed for PEEK frameworks veneered with composite paste used for screw-retained restorations, indicating that the insertion of screw channels weakened the PEEK frameworks [1]. Moreover, zirconia implant-supported frameworks with cantilevers showed higher fracture resistance than PEEK-based materials [34].…”
Section: Implant-supported Fixed Dental Prostheses (Ifdps)mentioning
confidence: 96%
“…On the other hand, Preis et al in a fatigue testing of PEEK molar crowns either bonded or screw-retained found lower fracture resistance than zirconia ones, while a total failure rate was observed for PEEK frameworks veneered with composite paste used for screw-retained restorations, indicating that the insertion of screw channels weakened the PEEK frameworks [1]. Moreover, zirconia implant-supported frameworks with cantilevers showed higher fracture resistance than PEEK-based materials [34].…”
Section: Implant-supported Fixed Dental Prostheses (Ifdps)mentioning
confidence: 96%
“…The use of a PEEK resin composite associated with glass fibers (Trinia ®, Shofu, Dental Corporation, San Marcos, CA, USA) as prosthetic infrastructure has been proposed, providing strength of 254.2 (22.3) MPa and an elastic modulus of 7.2 (3.5) GPa obtained in three-point-bending tests 19 . This material has been applied to fixed prostheses on implants by several authors with promising results [73][74][75] . The present investigation enabled to affirm that carbon/epoxy composites meet that requirement in all stress concentration condition, however, in the carbon/PPS needs further investigation as it has lower flexural properties, but it may overcome other disadvantage such as sudden failure presented in carbon/ epoxy composites.…”
Section: Discussionmentioning
confidence: 99%
“…Similar previous studies with same design were considered when determining the sample size and specimen fabrication. 13,29 In previously published studies done by the same group, using the identical test set up in this study and 5 specimens per group allowed the detection of significant differences amongst groups. Specimens were fabricated integrating a Ti base standard tessellation language (STL) in the design for a Ti base (Dmaster Dental Implants) to be later cemented.…”
Section: Introductionmentioning
confidence: 93%